Numerical Modeling Of One-Dimensional Overland Flow Over Porous Surface - Tah, Ai Sher (2019)
Due to rapid urbanization, surface water drainage systems are designed to perform as natural drainage acting as water storage areas that allow infiltration and evaporation. Furthermore, in order to solve issues caused by traditional drainage systems, there has been an increase of attention on Sustainable Urban Drainage systems (SuDs). Thus, to manage storm water, a simple yet efficient numerical model for flow over porous media is needed. The purpose of this research is to develop a numerical model for the simulation of flow over porous media. The model solves the unsteady one-dimensional shallow water equation. The accuracy of the numerical solution of the advection term in the momentum equation is increased by adopting the Constrained Interpolation Profile (CIP) scheme which is of the third order accuracy. The numerical model was firstly verified by simulating the dam-break flow problem. It was then validated against physical experiment of dam-break flow over porous bed. The author found that the numerical model performed satisfactorily in terms of surface flow profile and the loss of volume of flow through infiltration. This study found that the relationship of experimental data and numerical data has good agreement between each other with a discrepancy ratio of experimental data over numerical data ranging from 0.716 to 1.031. Besides, the flow front propagation is proportional to time with the 4/5 exponent power of (